2014
DOI: 10.1038/ncb3000
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5 marks stem/progenitor cells in ovary and tubal epithelia

Abstract: The ovary surface epithelium (OSE) undergoes ovulatory tear and remodelling throughout life. Resident stem cells drive such tissue homeostasis in many adult epithelia, but their existence in the ovary has not been definitively proven. Lgr5 marks stem cells in multiple epithelia. Here we use reporter mice and single-molecule fluorescent in situ hybridization to document candidate Lgr5(+) stem cells in the mouse ovary and associated structures. Lgr5 is broadly expressed during ovary organogenesis, but becomes li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
207
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(225 citation statements)
references
References 26 publications
13
207
4
1
Order By: Relevance
“…Exploiting transgenic mice which allow lineage tracing of cells expressing transcripts from the Lgr5 promoter, it was shown that LGR5-expressing OSE reside predominantly in the hilum, but over time give rise to LGR5 K OSE covering the entire ovary. More recently, Ng et al (2014) have confirmed the utility of LGR5 expression for the identification of putative OSE stem cells; however, in contrast to Fleskin-Niitin et al (2013), LGR5 expressing cells were found not only in the hilum region, but also throughout the surface of the ovary with highest concentrations noted in inter-follicular regions and regions adjacent to ovulatory rupture wounds. Lineage tracing suggested that multiple LGR5 C cells are recruited to effect ovulatory wound repair, and the location of these LGR5 C stem cells at inter-follicular regions may be important for the rapid repair of ovulatory wounds (Ng et al 2014).…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 81%
See 1 more Smart Citation
“…Exploiting transgenic mice which allow lineage tracing of cells expressing transcripts from the Lgr5 promoter, it was shown that LGR5-expressing OSE reside predominantly in the hilum, but over time give rise to LGR5 K OSE covering the entire ovary. More recently, Ng et al (2014) have confirmed the utility of LGR5 expression for the identification of putative OSE stem cells; however, in contrast to Fleskin-Niitin et al (2013), LGR5 expressing cells were found not only in the hilum region, but also throughout the surface of the ovary with highest concentrations noted in inter-follicular regions and regions adjacent to ovulatory rupture wounds. Lineage tracing suggested that multiple LGR5 C cells are recruited to effect ovulatory wound repair, and the location of these LGR5 C stem cells at inter-follicular regions may be important for the rapid repair of ovulatory wounds (Ng et al 2014).…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 81%
“…The somatic stem cells in the OSE have been investigated in three distinct contexts: potential stem cells able to regenerate germ cells (Parte et al 2011, Patel et al 2013, Virant-Klun et al 2013a, potential stem cells that give rise to granulosa cells (Hummitzsch et al 2013), and more traditional somatic stem cells whose role is to replenish the OSE following ovulatory wounding (Szotek et al 2008, Motohara et al 2011, Usongo & Farookhi 2012, Auersperg 2013, Flesken-Nikitin et al 2013, Ng et al 2014. While this review focuses briefly on studies that have addressed somatic stem cells that are thought to be required for ovulatory wound repair, the relationship with the HGSEOC of the two former potential stem cell pools cannot be discounted.…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 99%
“…Based on present research, Lgr5 seemed the most likely candidate of these genes to putatively mark the nail stem cells. Functional experiments and genetic lineage analyses have established that Lgr5 is a stem cell marker of both the intestinal epithelium and the hair follicle (17,18), and recent experiments have shown it to mark epithelial stem cells in additional tissues, including the stomach, mammary gland, tongue, and ovary (27)(28)(29)(30). In most of these cases, Lgr5 expression is driven by canonical Wnt signaling, placing Lgr5 in a feed-forward loop to maintain high Wnt signaling within Lgr5-expressing stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated, inducible lineage tracing methods using Cre/loxP transgenic mice are now available that can be used to throw a genetic switch to label a chosen cell population with a fluorescent or histochemical marker that will identify them and all their mitotic progeny. Such methods have been used to trace stem cell lineages in other tissues, including the hair follicle [97] , intestinal epithelium [98][99][100] and ovarian surface epithelium [101] , and this approach could be used to help resolve the LESC vs CESC debate. A similar approach has already been used, in conjunction with a multicoloured reporter construct, to trace clonal lineages in the ocular surface of zebrafish and demonstrate that, as in mice, the initial patchwork of cells established in the embryo is replaced by a radial pattern of clones that extend from the limbus [102] .…”
Section: Lineage Tracing Experimentsmentioning
confidence: 99%